Design conception and evaluation of an unmanned amphibious aerial vehicle using systematic approach - Surendar Ganesan; Balasubramanian Esakki; Silambarasan Mathiyazhagan; Vikram Pandimuthu (Aviation, 2022)
This article’s incitement interprets Unmanned Amphibious Aerial Vehicle (UAAV)’s conceptual design process in a systematic approach. The UAAV is conceptualised to be an ideal tool for limnologists in water quality assessment. Integration of hovercraft with the multi-rotor system helps collect water samples from remote and inaccessible water bodies. The UAAV flies in multi-rotor mode, subsequently land and glide along the water surface in hovercraft mode. The new and unconventional vehicle configuration makes the conceptual stage a challenging one in the design process. To overcome the challenges and strapped configuration of vehicle design, the Authors used a systematic approach of scenario-based design, morphological matrix, and Pugh’s method in the design process of the “Pahl & Beitz” model to retrieve the best possible UAAV design. The conglomerate design of UAAV is evaluated for its design requirements, and the computational analysis is performed to examine the mechanical strength and flow characteristics of UAAV. The experimental prototype of UAAV demonstrates the competence of flying in the air and hovering in water through field trials.